Saving the World at Business School. A Conversation with Andy Hoffman. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-dept, remotely filmed conversation in December 2020 between Howard Burton and Andy Hoffman, Holcim Professor of Sustainable Enterprise at the University of Michigan's Ross School of Business and School of Environment and Sustainability. They discuss Andy Hoffman's research and scholarly insights which are extremely relevant to today's society. Andy Hoffman is passionately committed to encouraging fellow academics to play a much stronger role in communicating knowledge, facts and information to the regular public and politicians which has culminated into his two new.